Safety of biological therapy in children and adolescents with severe asthma during the COVID-19 pandemic: a case series. - Votto, Martina; Santi, Viola; Bajeli, Marta; De Filippo, Maria; Deidda, Elisa; De Stefano, Emanuela; Dianin, Francesco; Raviola, Chiara; Silvi, Cecilia; Marseglia, Gian Luigi; Licari, Amelia (Acta Biomedica Atenei Parmensis, 2022)
Background and aim It is still unclear whether patients with severe asthma are at greater risk of developing severe COVID-19, particularly pediatric allergic patients under biologic therapy. Studies targeting pediatric patients are currently limited; thus, this study aims to assess the clinical characteristics of young patients with severe asthma under biological therapies during the COVID-19 pandemic. Methods We collected data from February 2020 to April 2021. Patients with severe asthma treated with biological therapies (omalizumab and mepolizumab) have been enrolled. We described demographic data, clinical features, therapies, comorbidities, and laboratory findings for each patient. For patients who got COVID-19, we also described the severity of the disease, the need for hospitalization, and specific therapy. Results A total of 14 patients were included in the study, 11 (78.6%) of them under treatment with omalizumab and 3 (21.6%) with mepolizumab. We identified four patients (28.6%) who tested positive for SARS-CoV-2. Two patients treated with mepolizumab had an asymptomatic disease, and two patients treated with omalizumab had mild disease. Only one patient with mild COVID-19 required hospitalization and specific therapy because of severe obesity. Conclusions No differences regarding the SARS-CoV-2 infection have been found between the two treatments groups. Furthermore, any poor outcome has been observed, confirming the safety of biological therapies. The limited number of patients enrolled and the lack of a control group did not establish a significant risk for infections for these patients.